Segurança na cirurgia da tiróide: neuromonitorização e selagem vascular - Torres Morientes, Luis Miguel; Tamayo Gómez, Eduardo; Invencio da Costa, Liliana Filipa; Mesonero, Marta Alonso; San Millán González, María; Santos Pérez, Jaime (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2024)
Introduction: Thyroid surgery carries significant risks and complications such as recurrent laryngeal nerve paralysis and postoperative suffocating hematoma. The most recent advancement providing safety is intraoperative neuromonitoring (IONM) of the recurrent laryngeal nerve (RLN) and the advances in hemostasis systems. Objective: The main objective of the study was to explore our experience regarding safety measures and the reduction of complications in thyroid surgery. Materials and Methods: We present a review of 400 neck surgeries performed by the same surgeon, from September 2011 to February 2020. The main variables studied were intraoperative neuromonitoring (IONM) of the recurrent laryngeal nerve and vascular sealing hemostasis systems. Results: Out of the total 400 patients, a total of 625 RLNs were studied, using IONM. Thirteen unilateral vocal cord paralyses were recorded, 8 of which were temporary and only 5 definitive. The predominant hemostasis system utilized was the vascular sealing system and bipolar clamp 87%, and in 13%, ligation of a thyroid artery. Only 1 patient experienced postoperative hemorrhage, which was resolved without incidents. Conclusions: Intermittent intraoperative neuromonitoring of the RLN and advances in hemostasis systems have proven to be valuable in thyroid surgery, improving safety and saving surgical time.